Menguasai Ketidakpastian: Strategi dan Keterampilan Membentuk Pembelajaran Masa Kini - Sevtriani, Melanny; Asbari, Masduki; Amaria, Laila; Muhammad, Banginda; Maulana, Akbar (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to understand how to Master Uncertainty to shape modern learners. In this research report, a qualitative descriptive method is used, with data sourced from listening to the spoken narrative on Gita Wirjawan's YouTube channel titled